TRANSFORMASI PROSEDUR MONITORING KEGIATAN MAINTENANCE ATAS PENJUALAN DAN SEWA MESIN - Amalia Eslyana Resti Putri (2023)
With the times, companies engaged in the banking industry have also experienced an increase in terms of sales. The increase in sales that occurred when the company made changes to the internal information system to support more regular monitoring and maintenance performance. There is an increase in the internal information system, it will input data again, especially in the customer data section, which is the main factor in the internal information system. The writing method used is a qualitative method, the data sources used come from observation, interviews and literature. The purpose of this writing is to find out the development of an internal information system regarding monitoring of maintenance activities on sales and rental of machines as well as the constraints faced by the company to evaluate the company's performance. With the development of an internal information system, it reduces the amount of fines that companies will pay to customer, fines occur due to a lack of features in the old information system, causing a relatively large amount of fines